Analisis Hukum Terhadap Penyampaian Informasi Elektronik yang Melanggar Norma Moral - Agustini, Shenti; Tan, Winsherly; Geovanni, Grace (Universitas Serang Raya, 2023)
This research aims to analyze the legal aspects of electronic information dissemination that violates moral norms. The unethical dissemination of information, including hoaxes, hate speech, and other harmful behaviors, has become a significant concern in the digital environment today. The research method employed is normative legal research, utilizing three approaches: legislative, case-based, and conceptual. Research data were collected from secondary sources, including relevant laws and literature on legal issues related to electronic information dissemination. Additionally, tertiary data was derived from specific cases that exemplify the phenomenon of morally unethical information dissemination empirically, both within the digital space and outside the network. Data analysis involved stages of reading, note-taking, reduction, interpretation, and concluded with deduction. The research results outline the pertinent articles and sections within legal regulations concerning violations of moral norms in electronic information dissemination. Furthermore, the study discusses law enforcement measures that can be taken against the perpetrators of such violations. This research contributes to understanding the legal aspects related to morally unethical electronic information dissemination in the current digital era. It is essential to ensure that ethics and legal compliance are maintained in the increasingly complex online environment.